Peran Pengetahuan dan Sikap Penderita terhadap Perilaku Pencarian Pengobatan Tuberkulosis Paru di Puskesmas Kecamatan Jatinegara Tahun 2013 - Revie Fitria Nasution; Arari Seruni (Jurnal Persada Husada Indonesia, 2014)
Indonesia as a developing country is a country with one of the highest pulmonary TB patients, 5th in the world after India , China , South Africa and Nigeria . In Indonesia pulmonary TB is the number one cause of death among infectious diseases and the third cause of death after cardiovascular disease and respiratory disease in all age groups. Treatment seeking behavior is a common attempt to address the health problems or illness to be cured by attending medical care facilities. Treatment seeking behavior is one person's decision when dealing with health issues due to related behavior of the public perception about the concept of health and illness. The purpose of this research is to understand how much attitude and knowledge play a role in the treatment seeking behavior of pulmonary tuberculosis patients. This research is a quantitative study using observational analytic epidemiologic design with cross sectional approach, in which the risk factors and the effects were measured and observed simultaneously at the same time. The respondents were pulmonary TB patients who are still undergoing active treatment in the study period with the total of 31 respondents. Results obtained from this study showed very good result in the respondents' attitudes toward the search for better treatment of pulmonary tuberculosis in sub-district Jatinegara Health Centers, this result plays an important role in the formation of pulmonary TB treatment seeking behavior, where respondents who had an attitude to search for better pulmonary tuberculosis treatment have 21.333 times better pulmonary TB treatment seeking behavior compare to respondents who did not search for better pulmonary tuberculosis treatment.